Empirical study on specific absorption rate of head tissues due to induced heating of 4G cell phone radiation - Christopher, B.; Mary Y, S.; Khandaker, Mayeen Uddin *; Jojo, P.J. (Elsevier, 2021)
Exposures to electromagnetic radiation mainly from the extended use of mobile phones may initiate biological damages in the human body at the macromolecular level. Several studies on human and animal models have shown significant changes in the functions of neural cells. Present empirical study analyses the thermal changes and the specific absorption rates (SAR) of brain, eye and skin tissues due to prolonged exposure to mobile phone radiation. A phantom, simulating human head with skin, skull and brain was used for the study. The Phantom was exposed to radiation for longer durations (600 s and more) and the temperature variations at different specific points were studied with sensitive thermocouple probes. SAR (1 g of contiguous tissue) values were determined using the variations of temperature and other parameters. The average rise in brain temperature was found to be 0.10 0.05 °C at 30 mm deep in the brain and the estimated SAR was 0.66 ± 0.35 Wkg-1. The increase in temperature for the eye socket was 0.03 ± 0.02 °C with SAR 0.15 ± 0.08 Wkg-1. The average rise in temperature for skin was 0.14 ± 0.05 °C and the SAR was 0.66 ± 0.42 Wkg-1. Although the measured SAR lie within the safe limit of 2 Wkg-1 recommended by the international regulatory body, considering the tremendous growth in the number of mobile phone users and prolonged use of mobile phone in communication purposes, the cumulative effects could be a real concern for human health.